Bank-Branch Supply, Financial Inclusion, and Wealth Accumulation - Célerier, Claire; Matray, Adrien (Review of Financial Studies, 2019)
Abstract This paper studies how financial inclusion affects wealth accumulation. Exploiting the U.S. interstate branching deregulation between 1994 and 2005, we find that an exogenous expansion of bank branches increases low-income household financial inclusion. We then show that financial inclusion fosters household wealth accumulation. Relative to their unbanked counterparts, banked households accumulate assets in interest-bearing accounts, invest more in durable assets, such as vehicles, have a better access to debt, and have a lower probability of facing financial strain. The results suggest that promoting financial inclusion for low-income populations can improve household wealth accumulation and financial security. Received April 13, 2017; editorial decision November 14, 2018 by Editor Stijn Van Nieuwerburgh. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.